KEABSAHAN AKTA HIBAH NO. 513/2018 YANG DIBUAT OLEH PPAT SRI SUSILOWATI S.H BERDASARKN KETENTUAN HUKUM TANAH NASIONAL (STUDI PUTUSAN NOMOR 1/PDT.G/2019/PN.SGI): Validity of Grant Deed No. 513/2018 Made By PPAT Sri Susilowati S.H Based on National Land Law (Study Of Judgement Number 1/Pdt.G/2019/PN.Sgi) - Salsabillah Galuh A; Metty Soletri (Universitas Trisakti, 2024)
Cancellation of the grant deed by the court as has occurred in the case in Sigli City in case Number 1/Pdt.G/2019/PN.Sgi. where Anita Binti Admi unlawfully granted disputed land to her son Harith Hasanuddin, even though the land based on AJB No: 521/x/PPAT/1998 had been purchased by the late Teuku Zainal from Anita and then by Teuku Zainal it was granted to Cut Aida. Without Cut Aida's knowledge, the land had been registered by Anita for submission of a Certificate based on the Deed of Grant issued by PPAT Sri Susilowati SH, meaning that PPAT Sri Susilowati deliberately abused her authority by issuing a Deed of Grant with Number: 513/218 for an object that did not actually belong to the Anita Bint Admi. The main issues raised are 1.) Legitimacy of the Deed of Grant No. 513/2018 made by PPAT Sri Susilowati S.H Based on National Land Law Provisions, 2.) Appropriateness of Judges' Considerations in Decision number 1Pdt.G/2019/PN, Sgi Based on National Land Law provisions. The type of research used is normative research with the nature of descriptive research to obtain secondary data. Besides that, the writer conducted a literature study. The data were analyzed qualitatively and conclusions were drawn using deductive logic. Deed of grant No. 513/2018L made by the Land Deed Making Officer Sri Susilowati SH is invalid because the material requirements for the transfer of land rights are not fulfilled.